Direct operating and portfolio management expenses: a case study of self storage facilities in South Africa within a global context - Van Der Linde, Adriaan Nicolaas (Department of Construction Economics and Management, 2018)
Self storage has become a globally recognised and specialised property investment. Valuation guidelines and annual Industry surveys are available for mature self storage markets worldwide, but currently there is no published South African guideline for self storage expense ratios in terms of total expenses, direct facility operating expenses and portfolio management expenses. These expenses, which are necessary for valuation, are difficult to obtain in the market compared to rental rates, which are publicly advertised to potential tenants. A case study approach was shown to be the applicable research methodology. It was then explained that the methodology consisted of four stages: The first stage describes the method of data collection from the valuation literature and international annual industry surveys. The second stage describes the method of data collection from the international self storage industry by analysing financial statements of international publicly listed self storage portfolios. The third stage describes the method of data collection from South African self storage portfolio case studies. The fourth stage describes how the data is to be analysed to arrive at an expense ratio guideline for South African self storage portfolios. The methodology was then carried out to answer the four research questions.